The sensitive nature of facial recognition: Tensions between the Swedish police and regulatory authorities - Eneman, Marie; Ljungberg, Jan; Raviola, Elena; Rolandsson, Bertil (Information polity, 2022)
Emerging technologies with artificial intelligence (AI) and machine learning are laying the foundation for surveillance capabilities of a magnitude never seen before. This article focuses on facial recognition, now rapidly introduced in many police authorities around the world, with expectations of enhanced security but also subject to concerns related to privacy. The article examined a recent case where the Swedish police used the controversial facial recognition application Clearview AI, which led to a supervisory investigation that deemed the police's use of the technology illegitimate. Following research question guided the study: How do the trade-offs between privacy and security unfold in the police use of facial recognition technology? The study was designed as a qualitative document analysis of the institutional dialogue between the police and two regulatory authorities, theoretically we draw on technological affordance and legitimacy. The results show how the police's use of facial recognition gives rise to various tensions that force the police as well as policy makers to rethink and further articulate the meaning of privacy. By identifying these tensions, the article contributes with insights into various controversial legitimacy issues that may arise in the area of rules in connection with the availability and use of facial recognition.